Occurrence of Aggregatibacter actinomycetemcomitans in Brazilian Indians from umutina reservation, Mato Grosso, Brazil - Vieira, Evanice Menezes Marçal [UNESP]; Raslan, Suzane A.; Wahasugui, Thais Cristina; Avila-Campos, Mario Julio; Marvulle, Valdecir; Gaetti-Jardim Júnior, Elerson [UNESP] (FapUNIFESP (SciELO), 2009)
Aggregatibacter actinomycetemcomitans is associated with periodontal disease, especially localized aggressive periodontitis, produces a potent leukotoxin and its distribution is influenced by ethnic characteristics of the population. Objective: Using culture and polymerase chain reaction (PCR) techniques, this study evaluated the occurrence of this microorganism and the distribution of leukotoxic strains isolated from Indians belonging to the Umutima Reservation, Mato Grosso, Brazil. Material and Methods: Forty- eight native Brazilians with gingivitis and 38 with chronic periodontitis, belonging to Umutina, Paresi, Bororo, Bakairi, Kayabi, Irantxe, Nambikwara and Terena ethnicities, were studied. Subgingival, supragingival and saliva samples of each patient were collected and transferred to VMGA III medium and to ultra pure Milli Q water. Bacteria were grown on TSBV agar and incubated in anaerobiosis (90% N2 + 10% CO2) at 37°C for 72 h. The presence of the ltx promoter was determined by PCR, and a 530 bp deletion in the promoter was evaluated by using specific primers. Results: A. actinomycetemcomitans was isolated from 8.33% of saliva, supragingival and subgingival samples from patients with gingivitis and from 18.42% of saliva and supragingival biofilm, and 26.32% subgingival biofilm from patients with chronic periodontitis. By PCR, the bacterial DNA was detected in 8.33% of saliva, supragingival and subgingival biofilms from patients with gingivitis and from 23.68% of saliva, 28.95% supragingival biofilm and 34.21% subgingival biofilm from patients with periodontitis. All strains were grouped as non-JP2 clones based on the absence of deletion in the leukotoxin promoter. Differences among the microbial and clinical parameters in patients were analyzed by using the Mann-Whitney, Chi-square or Fisher's exact tests. Conclusions: The present results suggest that A. actinomycetemcomitans can be related to the attachment loss in this population, but the presence of minimally leukotoxic strains, as well as its role in the pathogenesis of the periodontitis in these native Brazilians need to be further investigated.
Keywords: Bacteria; Gingivitis; Native Americans; Periodontitis